2010
DOI: 10.1055/s-0030-1248232
|View full text |Cite
|
Sign up to set email alerts
|

Distally Based Extended Peroneal Artery Septocutaneous Perforator Cross-Bridge Flap without Microvascular Anastomoses for Reconstruction of Contralateral Leg and Foot Soft Tissue Defects

Abstract: A cross-leg or cross-bridge free flap is one of the choices for the reconstruction of serious leg soft tissue defects. Here, we report on six cases of leg and foot reconstruction with a distally based extended peroneal artery septocutaneous perforator cross-bridge flap without microvascular anastomoses. The vascular pedicle includes the peroneal artery, its perforator branch, and concomitant veins. The total pedicle length ranges from 10 to 14 cm, and the size ranges from 18 x 8 to 21 x 10 cm. All flaps surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Our investigation confirmed that in the early 2010, Li et al 23 used this flap for reconstruction of knee defects with microvascular anastomosis.…”
Section: Discussionsupporting
confidence: 89%
“…Our investigation confirmed that in the early 2010, Li et al 23 used this flap for reconstruction of knee defects with microvascular anastomosis.…”
Section: Discussionsupporting
confidence: 89%
“…11,15,17,20,21,[33][34][35][36][37][38][39][40][41] The second most common reason cited as an indication to avoid free tissue transfer was the associated risk (12 of 56 publications, 107 of 322, 33.2% of patients). 14,21,32,37,[39][40][41][42][43][44][45][46] The third most common reason why free tissue transfer was not used was anatomic limitation (28 of 51 publications, n ¼ 170 of 322, 52.8% of patients) described in a variety of ways: no recipient vessels, inadequate vasculature, poor vascular supply, severe arterial injury, vascular damage, extensive zone of injury, lack of vasculature, one vessel run-off, or slight variations on the same language. 6,12,15,19,20,36,37,39,41,42,45,[47][48][49][50][51][52][53][54][55]…”
Section: Indications For Not Performing Free Tissue Transfermentioning
confidence: 99%
“…The majority of publications named the axial blood supply to the flaps described, though in 18 studies, 6,15,17,23,24,[27][28][29][33][34][35]37,45,46,50,52,55,60,63 the blood supply was unknown since it was not named, was described as random (used to describe as many as 136 patients) or was not easily inferred. Of those publications that did name an axial blood supply and made the number of patients with a given axial supply clear, the most common were the posterior tibial artery 25,36,38,42,43,48,53,[56][57][58]66 (11 of 37 publications, n ¼ 50 of 182, 27.5%) and peroneal artery 18,21,31,40,41,51,61,65 (8 of 37 publications, n ¼ 49 of 182, 26.9%) (►Fig. 4).…”
Section: Characteristics Of Transferred Tissuementioning
confidence: 99%
See 2 more Smart Citations